Middelbaar eindexamen Nederlands als vreemde taal in Hongarije - Szalai, Erika; Kántor-Faragó, Márta (Acta Neerlandica, 2015)
This article considers the examination methods for L2 learners in Hungary. A short history of past and current methods of examination for Dutch learners is covered in order to attest to the evolution in complexity and effectiveness that has taken place over the course of the years. The theoretical, statutory side of L2 examination is briefly taken into account, but the focus is on the practical aspect of L2 examination. The different elements of an ideal exam (reading, listening, writing and speaking proficiency, and correctness) are discussed with attention to detail and with the use of examples.